2009
DOI: 10.1093/nar/gkp1126
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimeric DNA methyltransferases as a platform for creating designer zinc finger methyltransferases for targeted DNA methylation in cells

Abstract: The ability to target methylation to specific genomic sites would further the study of DNA methylation’s biological role and potentially offer a tool for silencing gene expression and for treating diseases involving abnormal hypomethylation. The end-to-end fusion of DNA methyltransferases to zinc fingers has been shown to bias methylation to desired regions. However, the strategy is inherently limited because the methyltransferase domain remains active regardless of whether the zinc finger domain is bound at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…1 Our ability to selectively manipulate epigenetic status of functionally important genes is limited to suppressive methods, including RNA interference and targeted DNA-methyltransferases. 2 Mechanisms of DNA demethylation remain elusive, with postulates ranging from passive to enzymatic processes, as reviewed in reference 3. This contributes to our inability to create selective and/or gene-specific instruments to overcome silencing of genes switched off epigenetically.…”
Section: Introductionmentioning
confidence: 99%
“…1 Our ability to selectively manipulate epigenetic status of functionally important genes is limited to suppressive methods, including RNA interference and targeted DNA-methyltransferases. 2 Mechanisms of DNA demethylation remain elusive, with postulates ranging from passive to enzymatic processes, as reviewed in reference 3. This contributes to our inability to create selective and/or gene-specific instruments to overcome silencing of genes switched off epigenetically.…”
Section: Introductionmentioning
confidence: 99%
“…These co-dependent EEs can potentially increase the specificity of CME activity by requiring the binding of two distinct target sequences at the same locus. As examples of this approach, two studies targeted ZF fusions to DNA methyltransferase fragments [99, 100]. These studies showed that this strategy can yield a methyltransferase capable of significant levels of methylation at the target site with undetectable levels of methylation at non-target sites in Escherichia coli .…”
Section: Locus-specificitymentioning
confidence: 99%
“…For example, one group of investigators has reported the development of an interesting technology for promoting genomic locus-specific DNA methylation, using 2 different ZFs designed to bind to DNA flanking a target CpG site that are each fused with a component of a bifurcated DNA methyltransferase [115][116][117]. This approach aims to increase the local concentration of both methyltransferase fragments when the ZFs bind to the genome, leading to the assembly of an active methyltransferase enzyme only at the target site.…”
Section: Synthetic Biologymentioning
confidence: 99%